T-cells engineered with a novel VHH-based chimeric antigen receptor against CD19 exhibit comparable tumoricidal efficacy to their FMC63-based counterparts - Nasiri, Fatemeh; Safarzadeh Kozani, Pooria; Rahbarizadeh, Fatemeh (Frontiers in Immunology, 2023)
Background: Chimeric antigen receptor (CAR)-T cell therapy has established itself as a potent therapeutic option for certain patients with relapsed/refractory (R/R) hematologic malignancies. To date, four CD19-redirected CAR-T cell products have been granted the United States Food and Drug Administration (FDA) approval for medical use. However, all of these products are equipped with a single-chain fragment variable (scFv) as their targeting domains. Camelid single-domain antibodies (VHH or nanobody) can also be used as alternatives to scFvs. In this study, we developed VHH-based CD19-redirected CAR-Ts, and compared them with their FMC63 scFv-based counterpart. Methods: Human primary T cells were transduced to express a second-generation 4-1BB-CD3ζ-based CAR construct whose targeting domain was based on a CD19-specific VHH. The expansion rate, cytotoxicity, and secretion of proinflammatory cytokines (IFN-γ, IL-2, and TNF-α) of the developed CAR-Ts were assessed and compared with their FMC63 scFv-based counterpart as they were co-cultured with CD19-positive (Raji and Ramos) and CD19-negative (K562) cell lines. Results: VHH-CAR-Ts showed an expansion rate comparable to that of the scFv-CAR-Ts. In terms of cytotoxicity, VHH-CAR-Ts mediated cytolytic reactions against CD19+ cell lines, comparable to those of their scFv-based counterparts. Moreover, both VHH-CAR-Ts and scFv-CAR-Ts secreted remarkably higher and similar levels of IFN-γ, IL-2, and TNF-α upon co-cultivation with Ramos and Raji cell lines compared with while cultured alone or co-cultured with K562 cells. Conclusion: Our results demonstrated that our VHH-CAR-Ts could mediate CD19-dependent tumoricidal reactions as potently as their scFv-based counterparts. Moreover, VHHs could be applied as the targeting domains of CAR constructs to overcome the issues associated with the use of scFvs in CAR-T therapies.